Enhancing the capacity of fish-farmers and their support agents in understanding and using climate risk information at scale - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
A training dialogue on “Climate information services for aquaculture in Bangladesh” adaptable to fish-farmers and their support agents has shown immense potential in capacity building that support climate risk management. 20 participants from 15 institutions who, received the training during October 2019 at Bangladesh Meteorological Department (BMD), enhanced the capacity of nearly 46 support agents (fish-farm managers, hatchery managers, fish breeding professionals, extension staffs) and around 1237 fish-farmers for managing climate risks at scale.